Penyelesaian Perselisihan Hubungan Industrial Melalui Sistem Informasi Data Hubungan Industrial Kota Surakarta - Wahyu Safitri, Queentanti; Kusumawardhani, Arinta (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Industrial relations disputes between workers and employers that occur in Surakarta City companies can be filed with complaints to the Dinas Tenaga Kerja (DISNAKER) Kota Surakarta. The complaint will be followed up by a mediator. Results of the complaint process will be stored in the form of a recapitulation. To facilitate data recapitulation and data transparency so that the general public knows up to date to Bidang Hubungan Industrial DISNAKER Kota Surakarta, a Data Information System was created Surakarta City Industrial Relations (SIDHARTA). The aim of this research is to take steps to handle and obstacles to Settlement of Industrial Relations Disputes through the Surakarta City Industrial Relations Data Information System (SIDHARTA) at DISNAKER Kota Surakarta. The type of research carried out is using qualitative research methods with a focus on in-depth explanations based on experiences carried out when making observations related to observation targets, data sources, system components and obstacles through sources, activities carried out, location, and files used. Meanwhile, data collection techniques are consist of observation, interviews, and documentation. By including several components such as procedures, software, hardware, databases, networks and people. The research resulted in the conclusion that (SIDHARTA) has benefits as a database repository related to industrial relations and provides data transparency information to the people of Surakarta City. However, in its operation it still requires improvements that can be used optimally.